ՄԱԿ–ի գործունեությունը Իրաքում (2003 թ. մարտ – 2004 թ. հունիս) և հասարակական կարծիքի ձևավորումը - Սամվելյան, Կարինե («Զանգակ - 97»)
The article deals with the analyses of the achievements of the active role of the United Nations in Iraq in period of March 2003 - June 2004. It included the examination of Resolutions and Statements of the Security Council of the United Nations: Adjustments to Iraq-'oil-for-food' programme, Establishment of UN Assistance Mission for Iraq, Call for return of power to Iraqi pcople and etc.
Keywords: Պատմություն; Քաղաքականություն; Իրաք